Open access books: building blocks and policies - Snijder, Ronald; Mosterd, Tom (Septentrio Conference Series, 2022)
Watch the VIDEO.The complex realm of open science and scholarly communication consists of various increasingly interconnected parts. One of these building blocks is open access books. When taking a closer look at this particular building block, we see an intricate landscape of existing and emerging players, infrastructure, funding and policies. All these players and aspects play a role in a transition to open access for books as part of their larger open science policies.By focusing on the current state of affairs for this particular building block, we can describe the different stakeholders – commercial or community led – plus the roles they play and what infrastructure, metadata and identifiers are in place or still need to be developed. Furthermore, this session will take into account funding and policy developments related to open access books and its relation to the building block and open science as a whole.Based on this overview of the open access books landscape we invite the participants to discuss the implications for the larger goal of connecting the building blocks of Open Science. Enabling open science in this relatively small part of the scholarly communications realm comes with challenges for funders, publishers and libraries. Assuming that these challenges also exist for other open science building blocks, what can be learned from our experiences?
Keywords: open access books; metadata; persistent identifiers; research infrastructure; funder compliance